2005
DOI: 10.1073/pnas.0503125102
|View full text |Cite
|
Sign up to set email alerts
|

Targeting quantum dots to surface proteins in living cells with biotin ligase

Abstract: Escherichia coli biotin ligase site-specifically biotinylates a lysine side chain within a 15-amino acid acceptor peptide (AP) sequence. We show that mammalian cell surface proteins tagged with AP can be biotinylated by biotin ligase added to the medium, while endogenous proteins remain unmodified. The biotin group then serves as a handle for targeting streptavidin-conjugated quantum dots (QDs). This labeling method helps to address the two major deficiencies of antibody-based labeling, which is currently the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
473
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(478 citation statements)
references
References 42 publications
3
473
1
1
Order By: Relevance
“…[25][26][27][28] Although the specificity is very high, the large size (20-50 nm) of the conjugated antibody is a frequent concern. [29,30] Another approach is to attach a relatively small lipid to the QD directly to confer binding, [31] however the challenge is to retain aqueous solubility of the modified QD. Here we report a procedure for generating QDs which have affinity for the hydrophobic lipid-rich cell membrane while retaining aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Although the specificity is very high, the large size (20-50 nm) of the conjugated antibody is a frequent concern. [29,30] Another approach is to attach a relatively small lipid to the QD directly to confer binding, [31] however the challenge is to retain aqueous solubility of the modified QD. Here we report a procedure for generating QDs which have affinity for the hydrophobic lipid-rich cell membrane while retaining aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other nanoparticles, QDs can be modified via conjugation of various surface molecules for targeted delivery [33,34]. QDs also provide sufficient surface area to attach therapeutic agents for simultaneous drug delivery and in vivo imaging [35] as well as for tissue engineering [36]. In vivo cancer targeting and imaging in living animals by QDs was first demonstrated by Gao and colleagues [37], where both subcutaneous injection of QD-tagged prostate cancer cells and systemic injection of multifunctional QD probes were used to achieve sensitive and multicolor fluorescence imaging of cancer cells.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…It has been demonstrated that peptide tags can be labeled with biarsenical dyes (tetracysteine), nickel tris-nitriloacetic acid-conjugated dyes (oligohistidine) (see Table 2 for references), Texas Red ("fluorettes"), or biotin (biotin ligase acceptor peptides). Biotin ligase acceptor peptides are particularly advantageous because biotin ligases recognize cognate acceptor peptides with high specificity, and the use of different biotin ligases with orthogonal recognition specificities permits multiplex labeling [37,38]. Somewhat larger tags, derived from specific receptors and enzymes, have also been developed ( Table 2).…”
Section: Fluorescence Probes and Tagging Strategiesmentioning
confidence: 99%